MEDIATISASI LAYANAN PESAN ANTAR MAKANAN DI INDONESIA MELALUI APLIKASI GO-FOOD - Putra, Kadek Aryana Dwi; Hidayatullah, Fauzan; Farida, Nurul (Islamic Communication Journal, 2020)
In the era of digital technology the role of the media is very important in changing people's habits and becoming an important part in the lives of social communities. The existence of the media now greatly influences the culture of the community in obtaining information, but the negative side is that the media can control the community and make it subject to the rules made by the media itself. Go-food is present as a medium that makes it easy for people to meet the needs of high urban mobility. The business or trade sector is a sector that has an important role in the process of producing goods and services. The research method uses a cultural studies approach (cultural studies) in examining the Go-food phenomenon which is reflected in the socio-cultural context of the urban consumer society. Data collection techniques using the study of literature. The results showed that Go-food succeeded in mediating and changing the order of habits of users in meeting food needs through the media. There is a process by which the community begins to depend on the application and the existence of power which results in the community being subject to the rules that are made.